A Fundação da Liga Municipal de Desportos de São João Del-Rei e a constituição do esporte local nas páginas do jornal O correio (1941-1949) - Vinicius Eduardo Leite Batista (2018)
This work sought to understand and discuss the constitution of the sport - especially soccer - in São João del-Rei, Minas Gerais, between 1941 and 1949, based on the historical analysis of the local newspaper "O Correio". The foundation of the Municipal Sports League, which took place in 1944, was taken as the central point of discussion. The contextualization of this event took into account other motivations that contributed to the founding of this institution, such as the creation of the National Council of Sports by the government of Getúlio Vargas in 1941, and the closure in the same year of the Sport League West of Minas, organ that organized and fomented the local sport until then. In this way, with regard to the temporal cut, the year 1941 was established as the starting point for this investigation, closing in 1949, due to the scarcity of documentary sources and consequent decrease of elements that showed modifications considered relevant in the local football. This work looked for a qualitative nature by means of the survey and analysis of the correctness of the local newspaper "O Correio", which is stored next to the collection of the Baptista Caetano d'Almeida Library, in the city of São João del-Rei. It is hoped that this research will help in the historical understanding about the role of the local press, through the periodical "O Correio", for the process of organization of the local sport and characterization of soccer during the decade of 1940.